Querências afetivas: interconexões on/offline de mulheres cisgêneras e travestis negras - Sousa, Jéssica Silva de (2023)
Affected by the demands/debates of black women digitally and in person, in this research, I set out to investigate the affectivities of cisgender women and black travestis. For that, in this research I relied on elements of digital ethnography (MILLER, SLATER, 2004), and I tried to converge the bibliographical collections of the digital field with the interviews carried out in Fortaleza/CE, in the face-to-face field. References to Afro-diasporic and Afro-Brazilian productions prevailed in the research. Therefore, her work was based on escrevivência, a concept by Conceição Evaristo (2020) where I also read and analyzed the contexts and interlocutions through intersectionality (COLLINS, 2019; COLLINS, BILGE, 2020), elaboration of American black feminist thought, in dialogue with black Brazilian theoretical-political perspectives.